The secret of Indigo Moon - Taylor, G. P. (Taylor, G. P. Dopple Ganger chronicles, 2009)
Erik Morrissey Ganger and his friend, fourteen-year-old Sadie Dopple, meet a wealthy recluse while trying to escape tunnels under Isambard Dunstan's School for Wayward Children in order to pursue a former foe who has inadvertently kidnapped Sadie's twin sister, Saskia.